Applying Self-Determination Theory to Understand Public Employee's Motivation for a Public Service Career: An East Asian Case (Taiwan). Issue 2 (3rd April 2018) - Chen, Chung-An; Chen, Don-Yun; Xu, Chengwei
ABSTRACT: The research on employee motivation for choosing a public service career has largely been grounded in the intrinsic-extrinsic dichotomy along with limited motives such as job security, instrumental reward, and public service motivation (PSM). Such an approach narrows the view of researchers, especially those in cultures where major reasons for choosing a public service career exceed these factors and the intrinsic-extrinsic dichotomy. By employing self-determination theory (SDT) to examine data collected in Taiwan, an East Asian cultural setting, a measurement instrument is developed that captures five major motivations for a public service career. A discussion of applying this survey instrument for future research follows.